Pengaruh Live Shopee Terhadap Doom Spending Anggota Karang Taruna Kelurahan Gunung Terang Bandar Lampung - Sahri, Dilla Revira; Poyo, M. Denu; Waskito, Budhi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to measure the influence of Shopee's Live feature on Doom Spending behavior among members of the Karang Taruna in Gunung Terang Village, Bandar Lampung. The phenomenon of Doom Spending, which refers to impulsive shopping behavior triggered by stress or economic uncertainty, is increasingly prevalent among younger generations, particularly Gen Z and millennials. This research employs a quantitative approach using a survey method, where data is collected through questionnaires distributed to 60 Karang Taruna members. Data analysis is conducted using simple linear regression to examine the relationship between Shopee Live and Doom Spending. The findings are expected to provide a deeper understanding of how direct interactions in Shopee Live influence impulsive purchasing decisions and offer recommendations to mitigate the negative impacts of Doom Spending behavior.